Purification, Partial Characterizations, and N‐Terminal Amino Acid Sequence of a Procoagulant Protein FV‐2 from Daboia Russelli Siamensis (Myanmar) Venom. Issue 10 (11th May 2015) - Zhu, Weiwei; Wu, Zheng; Shen, Shuhao; Liu, Jun; Xiang, Nanlin; Liao, Yunjian; Lin, Xi; Chen, Lixin; Chen, Qi
ABSTRACT In this study, we purified and characterized the procoagulant protein FV‐2 from Daboia russelli siamensis (Myanmar) venom using ion‐exchange chromatography on CM‐Sephadex C‐50 and gel filtration on SuperdexTM G‐75 column. The activation of factor X and prothrombin was determined, respectively, by specific chromogenic substrates. The fibrinogen‐clotting activity, thermal stability, and pH stability were also determined. The N‐treminal sequence was determined by the National Center of Biomedical Analysis of China. In the end, FV‐2 was achieved with a molecular weight of 13, 608.0 Da. It could activate factor X, but did not affect prothrombin or fibrinogen. The suitable pH was 6.5–7.5, and the suitable temperature ranged from 25 to 60°C. The N‐terminal sequence was Asn‐Phe‐Phe‐Gln‐Phe‐Ala‐Glu‐Met‐Ile‐Val‐Lys‐Met‐Thr‐Gly‐Lys. Taken together, our studies suggest that FV‐2 is a factor X–activating enzyme, which can activate factor X to factor Xa, but it has no effect on prothrombin and fibrinogen.